2014
DOI: 10.1177/0969141314542115
|View full text |Cite
|
Sign up to set email alerts
|

Home-based screening for biliary atresia using infant stool colour cards: A large-scale prospective cohort study and cost-effectiveness analysis

Abstract: A BA ISCC screening programme targeting families of newborns is feasible in Canada. Passive distribution of ISCC at maternity is potentially effective and highly cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 24 publications
(36 reference statements)
1
53
0
Order By: Relevance
“…Moreover, the authors concluded that there was a greater than 97% likelihood that screening using stool color cards would result in a gain in life-years and a significant cost savings. Schreiber et al 27 conducted a prospective study in which infant stool color cards were distributed to more than 6000 families in the maternity ward of a Canadian women’s hospital. The authors used a variety of strategies to follow up on the infant stool color, from voluntary return of the cards at 30 days of age to follow-up with family physicians or families by random phone survey.…”
mentioning
confidence: 99%
“…Moreover, the authors concluded that there was a greater than 97% likelihood that screening using stool color cards would result in a gain in life-years and a significant cost savings. Schreiber et al 27 conducted a prospective study in which infant stool color cards were distributed to more than 6000 families in the maternity ward of a Canadian women’s hospital. The authors used a variety of strategies to follow up on the infant stool color, from voluntary return of the cards at 30 days of age to follow-up with family physicians or families by random phone survey.…”
mentioning
confidence: 99%
“…Because the SCC screening program is a feasible, cost-effective, and beneficial strategy for BA detection, 1214 it has currently been applied regionally or nationally in some countries including Brazil, Japan, Switzerland, Canada, and the Netherlands. 1318 …”
Section: Introductionmentioning
confidence: 99%
“…The exact percentage of infants with stool color change by 3 weeks of age, however, requires further study. Of importance, compared with the Phase 1 study conducted in BC, we had significantly higher SCC return rates (63% vs 26%) (13), which, we hypothesize, may be related to the engagement of the population in an already established urine home-based screening program.…”
Section: Discussionmentioning
confidence: 95%